Pengaruh Penambahan Telur Terhadap Elastisitas dan Penerimaan Mie Basah Bebas Gluten - Nita Maria Rosiana; Reta Qoirin Nisah (Jurnal Kesehatan, 2021)
70% childern with autism have gastointestinal problem due to the low amount of enzymes that hydrolyzed casein and gluten. As a result, protein can not be completely hydrolyzed into amino acids but only peptides. These petides lead to opioid receptors that cause behavioral disoders. Glutein and casein free diet can be one of the therapies for the treatment of behaviors disorders. The aims of this study were to determine the effects of addition eggs to the changes of elasticity of wet noodles from composite flour (mocaf flour, mung bean flour and tapioca flour), to know the panelist’s acceptance and to determine the nutritional facts of these noodles. The study design used randomized block design (RAK) with one factor, that is the addition of 4,5,6,7, and 8 eggs. The composite flour used was mocaf flour, mung bean flour and tapioca flour. The results showed that the addition of eggs had an effect on the elasticity of the wet noodle products with values ranging from 0.12 to 0.28N. The addition of 6 eggs produces noodles with the highest yellow color intensity, the most savory taste, there is the aroma of mung beans and eggs and the most elastic texture. The addition of eggs also increased the panelists' preference for noodle products. One bowl of noodles with a weight of 250 g contributes 12% of daily energy, 28% of daily protein needs, 12% of daily fat needs and 8% of daily carbohydrate needs. Gluten-free wet noodles from composite flour (mocaf flour, mung bean flour and tapioca flour) can be a main food alternative for people with autsim on a gluten-free diet. Keyword : autism, gluten free diet, noodles